What would a sociology applied to translation be like? - Fouces, Oscar Diaz; Monzó, Esther; Serpa, Tradução de Talita [UNESP]; Pinto, Paula Tavares [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2020)
The main purpose of this paper is to list some of the main sociological aspects to productively associate them with Translation Studies to promote the concept of Sociology Applied to Translation (SAT). This label was chosen because we intend to highlight the opportunity to attract resources, methods, and tools from other epistemological fields (those of the Social Sciences) and make a selective appropriation of them to our disciplinary scope. To do so, we draw a brief overview of studies, such as Wolf's (2002), Inghilleri's (2003), Sapiro's (2007), Sela-Sheffy's (2005), Thoutenhoofd's (2005) and Gouanvic's (2007) writings, among others. We absorb their analyses on concepts coming from different socio-cultural readings. Thus, we understand that such studies share a methodological structure and allow us to conceive valid hypotheses beyond specific moments in time, territorial spaces or social agents. This proposal will inspire the continuation and replication of research, and we hope that this inspiration will become a collective task undertaken by our area to promote the evolution of the SAT.
Como seria uma sociologia aplicada aos estudos da tradução?
Keywords: Sociology applied to translation; Sociology of translation; Translation studies